The Adobe InCopy CS2 book - Pratt, Adam (Adobe Press, 2006)
If you've ever worked in a fast-paced editorial environment, you know just how frustrating it can be to wait as each member of the team & ndash;from writer, to editor, to artist & ndash;makes changes to his or her piece of the layout puzzle. With InCopy, you don't have to! The Adobe InCopy Book shows editorial teams how to take control of the copy-fitting process as editors, designers, and writers work simultaneously on the same InDesign CS document. The guide begins with the basics, explaining what InCopy is and how it integrates with InDesign before moving on to describe the interface. The second section provides a feature-by-feature breakdown of how the program works, using simple step-by-step instructions and plenty of screen shots to ease the way. The remainder of the book is devoted to real-world workflows: one in which design trumps copy (that is, the design is created first), one in which copy trumps design (copy is created first), and one in which copy and design are of equal importance.